Effect of simulated microgravity and ionizing radiation on expression profiles of miRNA, lncRNA, and mRNA in human lymphoblastoid cells. (February 2020) - Fu, Hanjiang; Su, Fei; Zhu, Jie; Zheng, Xiaofei; Ge, Changhui
Highlights: Significantly downregulated lncRNAs and mRNAs identified with simulated microgravity. Significantly upregulated lncRNAs and mRNAs identified upon ionizing radiation. Simulated microgravity and radiation additively alter expression patterns of RNAs. Simulated microgravity and radiation synergistically alter expression levels of RNAs. Abstract: In space, multiple unique environmental factors, particularly microgravity and space radiation, pose a constant threat to astronaut health. MicroRNAs (miRNAs) and long noncoding RNAs (lncRNAs) are functional RNAs that play critical roles in regulating multiple cellular processes. To gain insight into the role of non-coding RNAs in response to radiation and microgravity, we analyzed RNA expression profiles in human lymphoblastoid TK6 cells incubated for 24 h under static or rotating conditions to stimulate microgravity in space, after 2-Gy γ-ray irradiation. The expression of 14 lncRNAs and 17 mRNAs (differentially-expressed genes, DEGs) was found to be significantly downregulated under simulated microgravity conditions. In contrast, irradiation upregulated 55 lncRNAs and 56 DEGs, whereas only one lncRNA, but no DEGs, was downregulated. Furthermore, two miRNAs, 70 lncRNAs, and 87 DEGs showed significantly altered expression in response to simulated microgravity after irradiation, and these changes were independently induced by irradiation and simulated microgravity. GO enrichment and KEGG pathway analyses indicated that the associated target genes showed similar patterns to the noncoding RNAs and were suggested to be involved in the immune/inflammatory response including LPS/TLR, TNF, and NF-κB signaling pathways. However, synergistic effects on RNA expression and cellular responses were also observed with a combination of simulated microgravity and irradiation based on microarray and RT-PCR analysis. Together, our results indicate that simulated microgravity and irradiation additively alter expression patterns but synergistically modulate the expression levels of RNAs and their target genes in human lymphoblastoid cells.